2017
DOI: 10.1021/jacs.7b07044
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Iron Sulfide for Highly Efficient Electrocatalytic Hydrogen Evolution

Abstract: We report a facile synthetic protocol to prepare mesoporous FeS without the aid of hard template as an electrocatalyst for the hydrogen evolution reaction (HER). The mesoporous FeS materials with high surface area were successfully prepared by a sol-gel method following a sulfurization treatment in an HS atmosphere. A remarkable HER catalytic performance was achieved with a low overpotential of 96 mV at a current density of 10 mA·cm and a Tafel slope of 78 mV per decade under alkaline conditions (pH 13). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
192
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(205 citation statements)
references
References 27 publications
2
192
0
Order By: Relevance
“…2c 46 In addition, density functional theory calculation revealed that sulfur was responsible for the active sites for proton adsorption and reduction; the high catalytic activity was stemmed from a large reduction of the kinetic energy barrier of H atom adsorption on FeS 2 surface upon Co doping in the iron pyrite structure. 18,19 The formation of heterostructures for Co-FeS 2 and CoS 2 further lowers the kinetic energy barrier of the reaction to gain superior electrocatalytic performance.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…2c 46 In addition, density functional theory calculation revealed that sulfur was responsible for the active sites for proton adsorption and reduction; the high catalytic activity was stemmed from a large reduction of the kinetic energy barrier of H atom adsorption on FeS 2 surface upon Co doping in the iron pyrite structure. 18,19 The formation of heterostructures for Co-FeS 2 and CoS 2 further lowers the kinetic energy barrier of the reaction to gain superior electrocatalytic performance.…”
Section: +mentioning
confidence: 99%
“…7,18 However, the catalytic performance of iron sulde is limited by its low surface area and lack of active sites. 19 If the non-noble metals electrocatalysts are grown on carbon material substrates, doping with homologous elements not only reduces the catalytic resistance but also exposes more active sites. [20][21][22] Furthermore, the formation of epitaxial heterostructures can regulate the energy barrier between the two interfaces to reduce the catalytic kinetic energy.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid Co 0.85 Se/graphene catalyst had al ow Ta fel slope of 34.4 mV dec À1 compared with that of unhybridized Co 0.85 Se (41.8 mV dec À1 ), suggestingaVolmer-Ta fel combination. [44] Introducing Mo to form MoÀFe selenide could modulate the electronic properties of the heterointerface and accelerate electron transfer from FeSe 2 to the active sites of 1T-MoSe 2 ,f acilitating the HER kinetics and resultingi nasmall Tafel slope of 57.7 mV dec À1 . [42] Leonard and co-workersh ave synthesized low-dimensional FeS 2 nanostructures and found that the 2D FeS 2 discs exhibited the highest electrocatalytic activity compared to the 1D FeS 2 nanowires and 3D FeS 2 cubes.…”
Section: Metal Chalcogenidesmentioning
confidence: 99%
“…Mesoporous FeS 2 with a high surface area was proposed as a promising alternative to Pt‐based electrocatalysts for water splitting. This material showed remarkable activity in the H 2 evolution reaction and had a low overpotential as a result of exposed (210) facets . Modified carbon materials are also promising electrocatalyst candidates; examples include mesoporous network‐like carbon doped with N and mesoporous carbon frameworks enriched with N and embedded with Cu and Co .…”
Section: Applications Of Nonsimpmsmentioning
confidence: 99%